2013
DOI: 10.1097/qad.0b013e3283606c11
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines and vascular health in treated HIV infection

Abstract: We examined the relationship between plasma adipokine concentrations and ultrasound measures of vascular health in 100 HIV-infected adults on antiretroviral therapy. Leptin was positively correlated with flow-mediated dilation of the brachial artery and negatively with carotid intima–media thickness. These relationships were independent of traditional risk factors and trunk fat in women but not men. Neither adiponectin nor resistin was associated with either measure of vascular health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(23 reference statements)
1
1
0
1
Order By: Relevance
“…In addition, recent study demonstrated that increases in body mass index (BMI) were not related to greater risk of CVD in PLWH on cART [68]. More importantly, plasma concentrations of leptin has been shown to be higher in patient on cART and increased levels of leptin was positively correlated with FMD and negatively with cIMT [69]. In agreement with this observation, our findings established the importance of leptin signaling in the protection of vascular function and health in PLWH.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, recent study demonstrated that increases in body mass index (BMI) were not related to greater risk of CVD in PLWH on cART [68]. More importantly, plasma concentrations of leptin has been shown to be higher in patient on cART and increased levels of leptin was positively correlated with FMD and negatively with cIMT [69]. In agreement with this observation, our findings established the importance of leptin signaling in the protection of vascular function and health in PLWH.…”
Section: Discussionsupporting
confidence: 88%
“…A similar effect of overweight/obese BMI on stroke risk in HIV infection was observed in the Kaiser Permanente California cohort[4]. Other studies have found a paradoxical association between higher BMI or plasma leptin, an adipokine directly correlated with fat cell mass, and lower cardiovascular risk[3335]. The association between higher BMI and stroke risk could be confounded by overall health status, as individuals with higher BMI may be healthier and have better control of their HIV infection.…”
Section: Discussionmentioning
confidence: 52%
“…В ряде перечисленных исследований проводилась поправка на курение как один из основных факторов сер- Более того, «парадокс ожирения», как уже говорилось, не является уникальным для сердечно-сосудистых заболеваний. Ряд исследований подтверждает положительное влияние повышенного ИМТ на выживаемость при СПИДе, терминальных стадиях хронической почечной недостаточности, что может быть частично объяснено запасом энергии в виде жира и повышенной мышечной массой в период распада белков [8,13,30].…”
Section: артериальная гипертония и ожирениеunclassified